On the relationship between moral virtue and philosophy in Republic - Posholi, Lerato (My University, 2015)
In this paper I investigate what I refer to as Plato’s necessity thesis. The thesis, as I understand it, states that some kind of moral virtue is necessary for making progress in philosophy. This means that only those with some sort of good character can make progress in philosophy. My objective in this paper is to understand what Plato might have meant by this thesis and to evaluate its plausibility. I show that the underlying justification for this thesis is what I call the similarity thesis. The central idea of this principle is that cognitive understanding of certain objects requires the knower to have a close kinship or similarity to the objects being studied. I then show the plausibility of the necessity thesis by showing how imperfect virtue, because of its likeness to the good, enables knowledge of the objects of philosophy.